O amigo do dinheiro: a visita do Cônego Garcia Velho Amaral aos Sertões do Norte de Baixo (1762-1766) - Silva Filho, José Rodrigues da (2018)
The present work has as its theme the pastoral visits in the Sertões do Norte de Baixo do Bispado of Pernambuco, from the case of the visit of the Côvo Garcia Velho do Amaral. The Sertoes of the North of Baixo are analyzed as a spatiality integrated to the bishopric of Pernambuco from the visits, as well as to analyze the circulation of the visiting priests in this Department and its influence in the visited parishes. The Pastoral Visits were an instrument of the prelates to try to establish in the parishes of Portuguese America, eighteenth century, the directives of the Council of Trent and to obtain information about the moral conduct of clerics and laity. The purpose of the views was before to intimidate, to maintain the possibility of a punishment, to punish. The visits, like the ecclesiastical justice itself, fought the sins transmuted into crime, on the argument that some sins were a cause of scandal. He was the bishop, according to the First Constitutions of the Archbishopric of Bahia, 1707, supported by the Tridentine Council, which was to visit his diocese. However, because of the territorial expanse of the bishoprics, the bishops in Portuguese America, very commonly, sent priests in their name, chosen among the most prominent clerics of the bishopric. The visit of the Canon Manuel Garcia Velho do Amaral to the parishes of the Sertões do Norte de Baixo, in the name of Bishop Francisco Xavier Aranha, occurred between 1762 and 1766. The procedure of the visitor motivated complaints to the prelate that, in response, issued a decree ordering that a summary of witnesses be prepared on the actions of Cônego Garcia do Amaral during his visit. A total of 96 witnesses were heard, from these reports it was possible to perceive the complaints that made the visit a target of a process. The testimonies contained in the summary also allowed the analysis of the faithful society of this spatiality and how the visits impacted this population.